BIOSORPTION, SOLUTION TO AS (V) POLLUTION - S. Akhtar; A. Shoaib (Journal of Animal and Plant Sciences, 2012)
The study was focused on exploring role of six agricultural wastes viz., wheat (Triticum aestivum L.) and rice (Oryza sativa L.) husk, pea (Pisum sativum L.), peanut (Arachis hypogaea L.), and banana (Musa acuminata L.) peels and sohanjana (Moringa oleifera Lam.) leaves for adsorption of As (V) from aqueous solution. Batch experiments were performed by taking 0.1 g of oven dried biomass of biosorbent in 250 mL flask containing 100 mL of 1 mg L-1 of As(V) solution at 150 rpm for 1 hour. The experiment was laid out as a completely randomized design with three replicates. Results indicates that all six adsorbents hold significantly greater adsorption capacity (0.99 mg g-1) and efficiency (99%) for capturing As(V) from the aqueous solution. Fourier Transformed Infrared Spectroscopy (FTIR) study revealed the involvement of carbohydrates and proteins groups like hydroxyl, amine, amide and carbonyl in metal sequestration. Adsorption based experiments summarized that agricultural wastes are potential easily available low-cost biomaterial for adsorption of As(V)ions from the aqueous phase.
Keywords: Metal; Arsenate; Adsorption; Agricultural waste